Keeping the Spirit of 1896 Alive: The Cooperative Movement Rising - Teodosio, Virginia A. (Philippine Journal of Labor and Industrial Relations; Vol 23 (2003): Philippine Journal of Labor and Industrial Relations, 2021)
This paper discusses the rise of cooperativism in the Philippines. Cooperatives are showing dynamism and effectiveness in pushing for a networked representation to achieve solidarity in scaling up their economic and social activities. This is being sustained by the inspired leadership of millionaire primary cooperatives in all parts of the country. Enormous changes have taken place in the cooperative movement and a transformation is underway. The cooperatives are varied in time and circumstances across the country and have created new needs and new problems. By the beginning of the 21st century, new technology, increased productivity and expanded markets have created a multitude of varying cooperative enterprises and consolidation. This paper highlights the accomplishments of select cooperatives and shows evidence of their transformational capacity.